An encoded viral micropatch for multiplex cell-based assays through localized gene delivery. Issue 14 (30th May 2017) - Han, Sangkwon; Bae, Hyung Jong; Kim, Su Deok; Park, Wook; Kwon, Sunghoon
Abstract : An encoded viral micropatch is presented for localized target gene expression for high-throughput, high-content cell-based assays. Abstract : The increasing number of potential drug targets and compounds has led to the development of high-throughput cell-based assays. Simultaneous processing of multiple targets in the same experiment based on localized target gene expression is a very efficient strategy for this purpose. To address this need, we present an adenoviral vector-immobilized microparticle with two-dimensional (2D) shape-encoding properties that allows localized patch-like gene delivery to monolayer-cultured cells. This format conveniently achieves multiplexed gene delivery compatible with both high-throughput cellular assays and fluorescence high-content imaging instruments. A multiplex G protein-coupled receptor (GPCR) internalization assay was developed to demonstrate the compatibility of this system with high-throughput image-based cellular assays.